Investigation and Modeling of the Electrical Bias Stress in Electrolyte‐Gated Organic Transistors. (15th May 2022) - Segantini, Matteo; Ballesio, Alberto; Palmara, Gianluca; Zaccagnini, Pietro; Frascella, Francesca; Garzone, Giovanna; Marasso, Simone Luigi; Cocuzza, Matteo; Parmeggiani, Matteo
Abstract: Electrolyte‐gated organic transistors (EGOTs) are emerging as an important tool in advanced biosensing applications. However, their widespread exploitation is still limited by their poor operational stability. In order to understand the causes of this unreliability, the proposed study focuses on the influence of electrical bias stress (EBS) on EGOTs operating in aqueous electrolytes. Poly(3‐hexylthiophene) (P3HT)‐ and poly[3‐(5‐carboxypentyl)thiophene)] (P3CPT)‐based transistors are studied under the application of a bias in the continuous and pulse mode. Combining electrical and spectroscopic characterizations, it is possible to ascribe the performance variation of P3HT devices to backbone rearrangements induced by side chain oxidation, hydration, and interfacial electrochemical doping at the semiconductor/electrolyte interface, while the presence of polar side chains in P3CPT enhances the oxidative degradation of the polymer throughout the bulk of the film. The charge‐trapping model based on a stretched exponential is commonly exploited for the description of EBS in solid dielectric organic field‐effect transistors (OFETs). The same model is here applied to fit liquid dielectric EGOT behavior. The extracted material parameters are in good agreement with those found in the literature for P3HT‐based OFETs. Finally, a novel improvement of the model is proposed to allow reproducing P3CPT data by accounting for its different degradation process. Abstract : The electrical bias stress in polythiophene‐based electrolyte‐gated organic transistors induces a degradation of the device performances given by an undesired ion intercalation in the polymeric film, which is enhanced by the polarity of the side chains. A model for the instability is proposed and it accounts for charge trapping and polymer degradation phenomena.